Pertinencia de la calidad educativa en los Posgrados del PNPC (2022)
This document aims to show an overview of factors that allude tothe assurance of educational quality at the higher level, specificallyof the Postgraduate Programs that belong to the National QualityPostgraduate Program (PNPC) of the National Council of Scienceand Technology (CONACYT). According to the PNPC Register inMexico, there are 2,435 master's and doctoral degrees recognizedby the PNPC, which in a given period are evaluated according toguidelines and criteria established by CONACYT. To this end, HigherEducation Institutions (IES) submit to an institutional commitment that supports the promotion, development and permanence of postgraduate courses, providing the necessary elements tocover the criteria and indicators evaluated. In this sense, basedon a qualitative methodology with a documentary approachand descriptive method, it was obtained that, in the case of theAutonomous University of Tabasco, the admission and permanenceof a postgraduate degree in the registry is strengthened in theeducational quality with actions in productivity, teaching, research,linking and mobility. Taking as a conclusion that the articulationof postgraduate courses entails institutional innovation processesthat establish patterns of strategies towards greater scope in thequalitative and quantitative indicators of the PNPC's postgraduateeducational programs. that supports the promotion, development and permanence